Reduction of obstruction related bladder overactivity by the guanylyl cyclase modulators BAY 41‐2272 and BAY 60‐2770 alone or in combination with a phosphodiesterase type 5 inhibitor. Issue 8 (17th September 2014) - Füllhase, C.; Hennenberg, M.; Sandner, P.; Strittmatter, F.; Niedworok, C.; Bauer, R.M.; Gratzke, C.; Soler, R.; Stief, C.; Andersson, K.E.
Abstract Aims To assess the urodynamic effects of soluble guanylyl cyclase (sGC) stimulator, BAY 41‐2272, and activator, BAY 60‐2770, (which both are able to induce cGMP synthesis even in the absence of nitric oxide (NO)) alone or in combination with a phosphodiesterase type 5 (PDE5) inhibitor, vardenafil, in a model of partial urethral obstruction (PUO) induced bladder overactivity (BO). Methods Fifty‐six male Sprague–Dawley rats were used, 31 of them underwent PUO. Fourteen rats were used for Western blots to assess PDE5 and sGC expression. For drug evaluation cystometry without anesthesia was performed three days following bladder catheterization. Results Obstructed rats showed higher micturition frequency and bladder pressures than non‐obstructed animals (Intermicturition Interval, IMI, 2.28 ± 0.55 vs. 3.60 ± 0.60 min (± standard deviation, SD); maximum micturition pressure, MMP, 70.1 ± 8.0 vs. 48.8 ± 7.2 cmH2O; both P < 0.05). In obstructed rats vardenafil, BAY 41‐2272, and BAY 60‐2770 increased IMI (2.77 ± 1.12, 2.62 ± 0.52, and 3.22 ± 1.04 min; all P < 0.05) and decreased MMP (54.4 ± 2.8, 61.5 ± 11.3, and 51.2 ± 6.3 cmH2O; all P < 0.05). When vardenafil was given following BAY 41‐2272 or BAY 60‐2770 no further urodynamic effects were observed. PDE5 as well as sGC protein expression was reduced in obstructed bladder tissue. Conclusions Targeting sGC via stimulators or activators, which increase the levels of cGMP independent of endogenous NO, is as effective as vardenafil to reduce urodynamic signs of BO. Targeting the NO/cGMP pathway via compounds acting on sGC might become a new approach to treat BO. Neurourol. Urodynam. 34:787–793, 2015. © 2014 Wiley Periodicals, Inc.